2020
DOI: 10.15517/am.v31i3.40892
|View full text |Cite
|
Sign up to set email alerts
|

Quality of raw milk in the highland tropics of Nariño, Colombia

Abstract: Introduction. The production and commercialization of raw milk in Nariño, Colombia, follows microbiological and compositional standards on which payment for quality is made. However, quality can be affected during its transport after milking. Objective. To describe the microbiological and compositional quality of raw milk in the highland tropic. Materials and methods. The study was carried out in seven municipalities in the department of Nariño, Colombia, during the rainy season between February and July of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
1
2
1
1
Order By: Relevance
“…Our data showed that the profile level of CTT and FAMT increase by sampling levels. Similarly data was found by Islam et al (2018) and Tobar-Delgado et al (2020). Likewise, a significant interaction for this germ was observed between the area and sample collection chain in raw and pasteurized milk samples (Mengstu et al, 2023).…”
Section: Effect Of Season On Milk Qualitysupporting
confidence: 79%
See 3 more Smart Citations
“…Our data showed that the profile level of CTT and FAMT increase by sampling levels. Similarly data was found by Islam et al (2018) and Tobar-Delgado et al (2020). Likewise, a significant interaction for this germ was observed between the area and sample collection chain in raw and pasteurized milk samples (Mengstu et al, 2023).…”
Section: Effect Of Season On Milk Qualitysupporting
confidence: 79%
“…Findings of the present study for density agree with Nyokabi et al (2021), and disagree with previously research when concerning FP. The present work revealed that fat, protein and total dray sec were affected by collection point; while Millogo et al (2010), Tobar-Delgado et al (2020 and Nyokabi et al (2021) didn't find any. PC varied between farm level/delivery unit, while the fat level and TDS revealed significant variation between farm, tank before and after cooling and tank dairy unit.…”
Section: Effect Of Season On Milk Qualitycontrasting
confidence: 49%
See 2 more Smart Citations
“…Varios microorganismos y sus toxinas afectan la calidad de la leche, cuya presencia está directamente relacionada con distintos factores, entre ellos, las condiciones inadecuadas de manipulación (7), la temperatura de almacenamiento(8,9), el grado de exposición de la leche a la luz y al oxígeno, la limpieza de los utensilios y equipos empleados en la cosecha de leche, los cambios estacionales (10), el estado del suelo y la salud animal (9,11,12). Las bacterias que llegan a la leche pueden ser o no patógenas, lo que de cualquier manera puede afectar la salud de los consumidores o deteriorar la calidad de la leche necesaria para la elaboración de productos derivados (13,14).…”
Section: Introductionunclassified